(untitled) (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND: The impact of essential drugs programs has been quantified during early studies in Yemen and Uganda. INRUD members developed a systematic program to refine drug use indicators. The techniques for using the indicators have been well tested and can assess current treatment practices, compare the performance of various health facilities or prescribers or monitor/supervise drug use behaviours in a reproducible manner. OBJECTIVE: This study is conducted to analyse prescription patterns according to WHO/INRUD prescribing indicators and identify drug use problems like polypharmacy or overuse of antibiotics etc. Patient care indicators measured in the study help evaluate the healthcare from the provider’s and patient’s perspectives. MATERIALS AND METHODOLOGY: The study was conducted by collecting the pictures of prescriptions presented at the Pharmacy store of Tertiary Care Teaching Hospital. The prescribed drugs were then analysed according to WHO indicators. RESULT: The number of drugs per encounter (3.19± 1.59) was found to be higher than WHO optimal standards. Only 24.29% of drugs were prescribed by generic name and % were from the Essential Drug List. Encounters with injections (1.7%) were found to be low. The average consultation time (5 min 31 sec) was less than prescribed standards (>10mins). The majority of drugs were actually dispensed and adequately labelled (91.2% and 97.2%) resp. 44.3% of prescriptions had illegible handwriting.